Insights Into the Cultivable Bacterial Fraction of Sediments From the Red Sea Mangroves and Physiological, Chemotaxonomic, and Genomic Characterization of Mangrovibacillus cuniculi gen. nov., sp. nov., a Novel Member of the Bacillaceae Family - Sefrji, Fatmah O.; Marasco, Ramona; Michoud, Grégoire; Seferji, Kholoud A.; Merlino, Giuseppe; Daffonchio, Daniele (Frontiers in Microbiology, 2022)
Mangrove forests are dynamic and productive ecosystems rich in microbial diversity; it has been estimated that microbial cells in the mangrove sediments constitute up to 91% of the total living biomass of these ecosystems. Despite in this ecosystem many of the ecological functions and services are supported and/or carried out by microorganisms (e.g., nutrient cycling and eukaryotic-host adaptation), their diversity and function are overlooked and poorly explored, especially for the oligotrophic mangrove of the Red Sea coast. Here, we investigated the cultivable fraction of bacteria associated with the sediments of Saudi Arabian Red Sea mangrove forest by applying the diffusion-chamber-based approach in combination with oligotrophic medium and long incubation time to allow the growth of bacteria in their natural environment. Cultivation resulted in the isolation of numerous representatives of Isoptericola (n = 51) and Marinobacter (n = 38), along with several less abundant and poorly study taxa (n = 25) distributed across ten genera. Within the latest group, we isolated R1DC41T, a novel member of the Bacillaceae family in the Firmicutes phylum. It showed 16S rRNA gene similarity of 94.59%–97.36% with closest relatives of Rossellomorea (which was formerly in the Bacillus genus), Domibacillus, Bacillus, and Jeotgalibacillus genera. Based on the multilocus sequence analysis, R1DC41T strain formed a separated branch from the listed genera, representing a novel species of a new genus for which the name Mangrovibacillus cuniculi gen. nov., sp. nov. is proposed. Genomic, morphological, and physiological characterizations revealed that R1DC41T is an aerobic, Gram-stain-variable, rod-shaped, non-motile, endospore-forming bacterium. A reduced genome and the presence of numerous transporters used to import the components necessary for its growth and resistance to the stresses imposed by the oligotrophic and salty mangrove sediments make R1DC41T extremely adapted to its environment of origin and to the competitive conditions present within.